2016
DOI: 10.1155/2016/4536470
|View full text |Cite
|
Sign up to set email alerts
|

Endurance and Resistance Training Affect High Fat Diet-Induced Increase of Ceramides, Inflammasome Expression, and Systemic Inflammation in Mice

Abstract: The study aimed to investigate the effects of differentiated exercise regimes on high fat-induced metabolic and inflammatory pathways. Mice were fed a standard diet (ST) or a high fat diet (HFD) and subjected to regular endurance training (ET) or resistance training (RT). After 10 weeks body weight, glucose tolerance, fatty acids (FAs), circulating ceramides, cytokines, and immunological mediators were determined. The HFD induced a significant increase in body weight and a disturbed glucose tolerance (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 51 publications
3
41
0
2
Order By: Relevance
“…Hsp can be released into the circulation and exert an immune stimulatory effect by interacting with pattern recognition receptors, such as toll-like receptors, and thereby activate the host inflammatory response (Asea et al 2002;Johnson et al2006). Aerobic exercise training has been shown to decrease markers of inflammation in plasma (Mardare et al 2016). Despite this, even long duration resistance training could not decrease inflammation in some studies (Hansen et al 2011;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Hsp can be released into the circulation and exert an immune stimulatory effect by interacting with pattern recognition receptors, such as toll-like receptors, and thereby activate the host inflammatory response (Asea et al 2002;Johnson et al2006). Aerobic exercise training has been shown to decrease markers of inflammation in plasma (Mardare et al 2016). Despite this, even long duration resistance training could not decrease inflammation in some studies (Hansen et al 2011;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…We showed that the primary mechanisms for exercise-induced improvement of vascular function were enhanced eNOS-mediated NO production and reduced oxidative stress and inflammatory signaling in vascular endothelium (Lee et al 2011;Park et al 2012). Furthermore, recent studies reported that chronic exercise training suppressed activation of NLRP3 inflammasome in the adipose tissue of obese mice (Mardare et al 2016) and in the brain of ovariectomized mice (Wang et al 2016b). However, the effect of physical activity on NLRP3 inflammasome activation-associated vascular function in obesity is not tested elsewhere.…”
Section: Introductionmentioning
confidence: 83%
“…) and in HFD‐induced obese mouse adipose tissues (Mardare et al. ). However, no study has investigated the effects of physical activity on coronary vascular NLRP3 inflammasome in diet‐induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations